1986
DOI: 10.1093/nar/14.10.4281
|View full text |Cite
|
Sign up to set email alerts
|

DNA sequence of the herpes simplex virus type 1 gene encoding glycoprotein gH, and identification of homologues in the genomes of varicella-zoster virus and Epstein-Barr virus

Abstract: We have determined the sequence of herpes simplex virus type 1 DNA around the previously mapped location of sequences encoding an epitope of glycoprotein gH, and have deduced the structure of the gH gene and the amino acid sequence of gH. The unprocessed polypeptide is predicted to contain 838 amino acids, and to possess an N-terminal signal sequence and a C-terminal transmembrane sequence. Temperature-sensitive mutant tsQ26 maps within the predicted gH coding sequence. Homologous genes were identified in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
78
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 32 publications
2
78
0
Order By: Relevance
“…Marker rescue experiments located the genetic lesion of tsQ26 in an EcoRI to PvulI fragment corresponding to map units 0.301 to 0.304 (Weller et al, 1983). As noted by McGeoch & Davison (1986) this fragment lies within the coding sequence of gH. In this paper we show that tsQ26 contains an amino acid substitution in gH and we investigate the phenotype of the mutant.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…Marker rescue experiments located the genetic lesion of tsQ26 in an EcoRI to PvulI fragment corresponding to map units 0.301 to 0.304 (Weller et al, 1983). As noted by McGeoch & Davison (1986) this fragment lies within the coding sequence of gH. In this paper we show that tsQ26 contains an amino acid substitution in gH and we investigate the phenotype of the mutant.…”
Section: Introductionmentioning
confidence: 63%
“…The gene for this protein has been mapped, using intertypic recombinants, to the immediate left of the thymidine kinase gene in the prototype orientation of the virus genome (Buckmaster et al, 1984;Gompels & Minson, 1986), and sequencing studies in this region of the genome have revealed an open reading frame that would code for an amino acid sequence of the correct size with the properties of a transmembrane glycoprotein (Gompels & Minson, 1986;McGeoch & Davison, 1986). Although we know nothing of the functions of gH, two lines of evidence suggest that it plays a central role in the virus replication cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…VZV gplII is homologous with gH of herpes simplex virus (HSV) (McGeoch & Davison, 1986;Gompels & Minson, 1986;Davison & Scott, 1986). Both V3 (antigplII) and an anti-gplII murine MAb inhibit virus spread , which is similar to the activity of anti-gH antibodies (Buckmaster et al, 1984;Gompels & Minson, 1986).…”
Section: Discussionmentioning
confidence: 95%
“…Genes encoding glycoproteins gH and gL have been found in nearly all members of the family Herpesviridae (Davison & Scott, 1986 ;Gompels & Minson, 1986 ;McGeoch & Davison, 1986 ;Cranage et al, 1988 ;Gompels et al, 1988 ;Josephs et al, 1991 ;Meyer et al, 1991 ;Kaye et al, 1992 ;Klupp et al, 1992Klupp et al, , 1994Telford et al, 1992Telford et al, , 1993Telford et al, , 1995Xu et al, 1994 a, b ;Liu et al, 1993 ;Scott et al, 1993 ;Yoshida et al, 1994 ;Khattar et al, 1995 ;Moore et al, 1996). The only exception is channel MM ranging from 31-35 kDa and diffusely migrating protein species ranging from 45-65 kDa.…”
Section: Introductionmentioning
confidence: 99%